2016
DOI: 10.5114/ada.2016.61605
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intima-media thickness in patients with mild or moderate psoriasis

Abstract: IntroductionPsoriasis is a chronic inflammatory disease associated with a significantly higher morbidity and various comorbidities (obesity, metabolic syndrome, diabetes). Previous studies focused mainly on patients with severe psoriasis who were found to have increased markers of early atherosclerosis, higher intima-media thickness (IMT) values.AimTo evaluate the association between the severity or duration of psoriasis and carotid IMT in patients with mild and moderate psoriasis.Material and methodsWe studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
2
12
0
1
Order By: Relevance
“…Doppler examination of both common carotid arteries defined 40 psoriatic patients with CIMT of >0.9 mm, which is a cut-off point for diagnosis of AAS. 3 In line with these findings, Bańska-Kisiel et al 1 reported a high prevalence of early AS in psoriatic patients and concluded that psoriasis may contribute to an accelerated systemic inflammatory cascade resulting in increased risk of CV events. Fang et al 15 suggested that patients with psoriasis are associated with excessive risk of AAS and monitoring of CIMT may be recommended to identify psoriatic patients at a higher risk for CV events.…”
Section: Discussionmentioning
confidence: 74%
“…Doppler examination of both common carotid arteries defined 40 psoriatic patients with CIMT of >0.9 mm, which is a cut-off point for diagnosis of AAS. 3 In line with these findings, Bańska-Kisiel et al 1 reported a high prevalence of early AS in psoriatic patients and concluded that psoriasis may contribute to an accelerated systemic inflammatory cascade resulting in increased risk of CV events. Fang et al 15 suggested that patients with psoriasis are associated with excessive risk of AAS and monitoring of CIMT may be recommended to identify psoriatic patients at a higher risk for CV events.…”
Section: Discussionmentioning
confidence: 74%
“…Using carotid artery ultrasound, various studies have found that patients with psoriasis have greater carotid intima-media thickness compared to healthy controls, indicating carotid atherosclerosis [ 70 , 71 , 72 , 73 , 74 ]. The severity of skin disease (measured by Psoriasis Area and Severity Index (PASI) score) has been found to correlate with carotid intima-media thickness values [ 75 ]. A recent meta-analysis of 20 studies also confirmed that patients with psoriasis have greater carotid intima-media thickness values and decreased flow-mediated dilation compared to healthy controls, thus demonstrating an association between psoriasis and subclinical carotid atherosclerosis [ 76 ].…”
Section: Psoriasis and Atherosclerosismentioning
confidence: 99%
“…Psoriatic patients had a greater thickness of the intima-media complex of the internal carotid artery than the control group (0.61 ±0.01 mm vs. 0.37 ±0.01 mm) [7]. Then, Bańska-Kisiel et al [13] concluded that the severity of psoriasis measured by means of PASI showed a significant correlation with the values of intima-media complex of the internal carotid artery. Naik et al [14] used positron emission tomography/computed tomography (PET/CT) and showed that psoriatic patients undergo a more intensified inflammation within the aorta, and there exists a dependency between severity of psoriasis and the level of inflammation in the vessels.…”
Section: Sercowo-naczyniowychmentioning
confidence: 99%
“…Bańska--Kisiel i wsp. [13] stwierdzili, że ciężkość łuszczycy mierzona za pomocą PASI istotnie koreluje z wartościami kompleksu intima-media tętnicy szyjnej wewnętrznej. Naik i wsp.…”
Section: Sercowo-naczyniowychunclassified